A Review of Computational Drug Repositioning Approaches - Huang, Guohua; Li, Jincheng; Wang, Peng; Li, Weibiao (Combinatorial Chemistry & High Throughput Screening, 2017)
Aims & Scope: Computational drug repositioning emerges as a new idea of drug discovery and development. Contrary to conventional routines, computational drug repositioning encompasses low risk and high safety. Some successful cases demonstrated its advantage. Therefore, a large number of computational drug repositioning approaches have been developed over the past decades. We summarized briefly these methods and classified them into target-based, geneexpression- based, phenome-based and multi-omics-based categories according to strategies of drug repositioning. Conclusion: We reviewed some representatives of computational drug repositioning methods in each category, with emphasis on detail of techniques and finally discussed developing trends of computational drug repositioning.
Keywords: phenotype